PENDAMPINGAN PERANCANGAN DIGITAL MARKETING DAN E-COMMERCE BAGI PEMUDA DESA PAKIS DALAM MENDUKUNG DESA WISATA RENGGANIS - Kristiana, Arika Indah; Imsiyah, Niswatul; Kartini, Titin; Susanto, Susanto; Alfarisi, Ridho; Fatahillah, Arif; Safrida, Lela Nur (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTAs a tourist village, Pakis Village, Panti Jember subdistrict really needs to be promoted. Promotion of village tourism can be done using digital marketing or websites. This is the background for involving village youth in promoting village tourism. The solution offered is training and mentoring for village youth. This service activity is divided into two activities, namely training to provide material about e-commerce, digital marketing and websites, mentoring activities namely designing and managing websites. The stages in implementing community service are the preparation stage, training stage, website creation stage and mentoring stage. The number of participants for training and mentoring is 25 participants. Specifically, for the website admin, 3 young people were selected, 2 of whom were members of the youth organization and one person was a member of the village apparatus.Keywords: Mentoring, E-commerce, Digital marketing, Village websites, Tourist villagesÂ ABSTRAKSebagai desa wisata, Desa Pakis kecamatan Panti Jember sangat perlu untuk dipromosikan. Dalam promosi wisata desa dapat dilakukan menggunakan digital marketing atau website. Hal ini yang menjadi latar belakang pelibatan pemuda desa dalam promosi wisata desa. Solusi yang ditawarkan adalah pelatihan dan pendampingan bagi pemuda desa. Kegitan pengabdian ini dibagi menjadi dua kegiatan yaitu pelatihan untuk memberikan materi tentang e-commerce, digital marketing dan website, kegiatan pendampingan yaitu merancang serta mengelola website. Tahapan dalam pelaksanaan pengabdian adalah tahap persiapan, tahap pelatihan, tahap pembuatan website dan tahap pendampingan. Jumlah peserta untuk pelatihan dan pendampingan adalah 25 peserta. Khusus untuk admin website dipilih 3 pemuda dimana 2 orang sebagai anggota karang taruna dan satu orang sebagai anggota perangkat desa.Kata Kunci: Pendampingan, E-commerce, Digital marketing, Website desa, Desa wisata